Deteksi Dini Masalah Tumbuh Kembang Anak dalam Pendidikan Usia Dini - Ningsih, Syakdia Apria (TSAQOFAH, 2026)
Early detection of problems in child growth and development constitutes a strategic measure in the provision of Early Childhood Education (Pendidikan Anak Usia Dini/PAUD) to ensure that every child receives stimulation, interventions, and services that are aligned with their needs, given that early childhood is a period of very rapid development and heightened vulnerability to various disorders, thus requiring systematic, integrated, and continuous monitoring. This study aims to describe the urgency of early detection in identifying developmental deviations in children’s physical, cognitive, language, socio-emotional, and behavioral domains within the context of PAUD services. A literature review method was employed by examining various scientific sources related to child development and the implementation of PAUD services. The findings indicate that early detection provides significant benefits, including accelerating the handling of developmental problems, increasing the effectiveness of interventions, and assisting educators and parents in designing appropriate stimulation strategies. In addition, collaboration among educators, parents, and health professionals is a key factor in the successful implementation of early detection. Therefore, early detection needs to be systematically integrated into PAUD services to support optimal child growth and development and to prevent the emergence of more complex developmental problems in later life.